Community Punishment in the Resolution of Livestock Theft Cases (A Study on the Ambal-Ambal Group in Pringgasela Subdistrict, East Lombok Regency: Community Punishment dalam Penyelesaian Kasus Pencurian Hewan Ternak (Studi Pada Kelompok Ambal-Ambal di Kecamatan Pringgasela, Kabupaten Lombok Timur - Nirmala, Atika Zahra; Baiq Ishariaty Wika Utary (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2025)
Livestock theft particularly cattle is a serious issue in East Lombok, given the high economic and social value these animals hold for local communities. This study examines the practice of community punishment carried out by the Ambal-Ambal group in Pringgasela Subdistrict to resolve livestock theft cases. Employing an empirical legal research design with a socio-legal and case study approach, the study draws on both primary and secondary data, analyzed through qualitative descriptive methods. Findings reveal that conflict resolution prioritizes socio-economic restoration over repressive punishment. The identity of the offender is kept confidential, while sanctions typically involve productive community tasks or internal fines. In some cases, offenders even receive social assistance as an expression of communal solidarity. These findings affirm that community punishment serves as a culturally appropriate and effective alternative dispute resolution mechanism, deeply rooted in local values of brotherhood and social harmony.